2008
DOI: 10.1088/0957-4484/19/38/384003
|View full text |Cite
|
Sign up to set email alerts
|

AFM-based analysis of human metastatic cancer cells

Abstract: Recently biomechanics of cancer cells, in particular stiffness or elasticity, has been identified as an important factor relating to cancer cell function, adherence, motility, transformation and invasion. We report on the nanomechanical responses of metastatic cancer cells and benign mesothelial cells taken from human body cavity fluids using atomic force microscopy. Following our initial study (Cross et al 2007 Nat. Nanotechnol. 2 780-3), we report on the biophysical properties of patient-derived effusion cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
292
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(316 citation statements)
references
References 40 publications
13
292
0
5
Order By: Relevance
“…This is in agreement with reports that have shown that when directly comparing stiffness of adherent cancer and normal cells, cell stiffness is significantly increased in the cancer cells (40). However, there have also been contradicting reports of decreased cell stiffness and increased deformability of cancer cells (41)(42)(43)(44). Nevertheless, as these latter studies analyzed cells in suspension or nonspread cells, this discrepancy in cell stiffness changes might be explained by differences in the spreading of the analyzed cells.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with reports that have shown that when directly comparing stiffness of adherent cancer and normal cells, cell stiffness is significantly increased in the cancer cells (40). However, there have also been contradicting reports of decreased cell stiffness and increased deformability of cancer cells (41)(42)(43)(44). Nevertheless, as these latter studies analyzed cells in suspension or nonspread cells, this discrepancy in cell stiffness changes might be explained by differences in the spreading of the analyzed cells.…”
Section: Discussionsupporting
confidence: 91%
“…This is known as the "bottom effect" artefact that makes cell appear stiffer than they really are when thin samples are used. To avoid this artefact, usually the indentation is limited to 10% of the cell thickness [10]. In our study, we want to compare the local viscoelasticity of human bladder cancer cells, especially at the periphery, where the cell thickness is around 200 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies of a variety of diseases using different experimental techniques have shown that abnormalities are connected with the mechanical properties of cells, in particular in cancer metastasis [6,7]. In fact, this is a subject of controversy as some studies report a stiffening of cancer cells compared to benign cells [8], while others show that cancer is characterized by the decrease of the cell stiffness [9,10] i.e. metastatic cancer cells have an elastic modulus lower than that of healthy cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the medium's elastic modulus, which is directly related with the speed of sound in the medium, can be determined simply by measuring the Brillouin shift. Compared to other imaging techniques that are capable of quantifying material's mechanical properties (e.g., [8][9][10]), Brillouin spectroscopy offers a non-contact, non-invasive, and label-free contrast mechanism with microscopic spatial resolution. The microscopic elasticity of the living organisms enables investigations of cell mechanics with a sub-micron resolution, which is essential for understanding biological development and disease pathophysiology [11].…”
Section: Introductionmentioning
confidence: 99%